2012
DOI: 10.4021/jcgo47w
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ascorbic Acid on the Estrogen/Progesteron Levels in the Isolated Rabbit Uterine Muscle

Abstract: Background: The study was carried out to examine the effect of Ascorbic Acid (AsA) on estrogen/progesterone levels in the isolated non-pregnant rabbit uterine muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
5
1
1
Order By: Relevance
“…The current level is ranged between 47.3 to 89.0 pg/ml during the second half of pregnancy days. This level is slightly lower than that (98.1 pg/ml) found by Bostanci et al (2012). Conversely, our present level is much higher than other studies.…”
Section: Hormonal Changes In Pregnant Rabbit Doescontrasting
confidence: 92%
See 3 more Smart Citations
“…The current level is ranged between 47.3 to 89.0 pg/ml during the second half of pregnancy days. This level is slightly lower than that (98.1 pg/ml) found by Bostanci et al (2012). Conversely, our present level is much higher than other studies.…”
Section: Hormonal Changes In Pregnant Rabbit Doescontrasting
confidence: 92%
“…Additionally, the present data disagree and lower than those of Alfonso (2016) who found that, the highest level (12 ng/ml) of P4 was at day 14 of pregnancy, after that its level started to decrease at days 21 and 28 of pregnancy (10 and 8 ng/ml, respectively). On the other side, it is much higher than that (1.5 ng/ml) obtained by Bostanci et al (2012). Generally, the level of P4 hormone in rabbits during pregnancy is lower than that in other species, Neville et al (2002) stated that P4 in rat is ranged between 6-130 ng/ml, and reaching to 200 ng/ml in human.…”
Section: Hormonal Changes In Pregnant Rabbit Doesmentioning
confidence: 81%
See 2 more Smart Citations
“…Про це свідчить позитивний клінічний досвід застосування монокомпонентних вагінальних супозиторіїв з молочною кислотою «Фемілекс» [67]. За даними дослідників введення до складу таких препаратів аскорбінової кислоти може не тільки сприяти збереженню вагінального біотопу, але й підвищувати вміст естрогенів у тканинах генітального тракту [68]. Наявність антиоксидантних властивостей може бути корисним для відновлення про/антиоксидантного балансу, яке виникає внаслідок дефіциту естрогенів.…”
Section: проблеми ендокринної патології № 4 2018unclassified